2017
DOI: 10.1063/1.4983219
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of structure and dynamics in liquid antimony and Sbn clusters

Abstract: Density functional/molecular dynamics simulations have been performed on liquid antimony (588 atoms and six temperatures between 600 K and 1300 K) and on neutral Sb clusters with up to 14 atoms. We study structural patterns (coordination numbers, bond angles, and ring patterns, structure factors, pair distribution functions) and dynamical properties (vibration frequencies, diffusion constants, power spectra, dynamical structure factors, viscosity) and compare with available experimental results and with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 91 publications
(126 reference statements)
4
15
1
Order By: Relevance
“…Here, information on the kinetics of pure Sb could not be obtained due to its extreme tendency to crystallize. Ab initio molecular dynamics (AIMD) simulations based on density functional theory (DFT) have shown that pure Sb can crystallize very rapidly in the presence of crystalline Sb boundaries, with an extremely high growth velocity of ≈36 m s −1 at T = 600 K . Such a crystallization speed is much greater than that of Ge 2 Sb 2 Te 5 .…”
Section: The Local Structural Motifs In Amorphous Sb In15sb85 and Gmentioning
confidence: 99%
“…Here, information on the kinetics of pure Sb could not be obtained due to its extreme tendency to crystallize. Ab initio molecular dynamics (AIMD) simulations based on density functional theory (DFT) have shown that pure Sb can crystallize very rapidly in the presence of crystalline Sb boundaries, with an extremely high growth velocity of ≈36 m s −1 at T = 600 K . Such a crystallization speed is much greater than that of Ge 2 Sb 2 Te 5 .…”
Section: The Local Structural Motifs In Amorphous Sb In15sb85 and Gmentioning
confidence: 99%
“…We compare with experimental results, particularly quasielastic and inelastic neutron scattering [49][50][51] and inelastic x-ray scattering (IXS) [52], which provide information about collective excitations. The DF/MD method was used previously to study liquid Te [47], Bi [53], and Sb [54], and details are given in [53]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…TOFMS does not provide direct structural information and thus it is difficult to elucidate the structure of the generated clusters from the mass spectra itself. On the other hand, the structures of many gallium 4245 , antimony 4648 , and selenium 49,50 clusters are known. Apart from the aforementioned structures, only a few structures of the binary gallium selenide and antimony selenide clusters have been reported 51,52 .…”
Section: Resultsmentioning
confidence: 99%